2015
DOI: 10.1080/1357650x.2015.1084312
|View full text |Cite
|
Sign up to set email alerts
|

Right perceptual bias and self-face recognition in individuals with congenital prosopagnosia

Abstract: The existence of a drift to base judgments more on the right half-part of facial stimuli, which falls in the observer's left visual field (left perceptual bias (LPB)), in normal individuals has been demonstrated. However, less is known about the existence of this phenomenon in people affected by face impairment from birth, namely congenital prosopagnosics. In the current study, we aimed to investigate the presence of the LPB under face impairment conditions using chimeric stimuli and the most familiar face of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 77 publications
1
15
1
Order By: Relevance
“…All stimuli were displayed until the participant responded, by pressing corresponding buttons on a response box, to judge which of the two chimeric characters looked more similar to the original one The inclusion of non-linguistic stimuli such as faces will also help us understand whether the observed LSB and HP effects are related to impaired linguistic processing. In contrast to Chinese readers with dyslexia, people with prosopagnosia were reported to have reduced LSB (Malaspina et al, 2016) and HP (Avidan et al, 2011) in face perception. These findings suggest that the deficits may be related to difficulties in forming appropriate configural representations in the RH.…”
Section: Discussionmentioning
confidence: 71%
“…All stimuli were displayed until the participant responded, by pressing corresponding buttons on a response box, to judge which of the two chimeric characters looked more similar to the original one The inclusion of non-linguistic stimuli such as faces will also help us understand whether the observed LSB and HP effects are related to impaired linguistic processing. In contrast to Chinese readers with dyslexia, people with prosopagnosia were reported to have reduced LSB (Malaspina et al, 2016) and HP (Avidan et al, 2011) in face perception. These findings suggest that the deficits may be related to difficulties in forming appropriate configural representations in the RH.…”
Section: Discussionmentioning
confidence: 71%
“…To some extent this is offset by diagnostic approaches that require impaired performance on multiple tests within the same session (e.g. [69][70][71]), although the most popular tasks (CFMT, CFPT and famous faces) arguably tap different sub-processes of face recognition that can be selectively impaired in some individuals. Thus, the issue of repeat assessment on different versions of the same test is particularly pertinent in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, previous findings seem to support the idea that, along with the inability to recognize familiar and unfamiliar faces and the presence of an anomalous scan path behavior, individuals with CP explore every face in the same way, independently of whether the face is familiar (or famous) to them or not. However, recent findings have demonstrated that despite their face recognition impairment, congenital prosopagnosics (Malaspina, Albonico & Daini, 2016) achieve considerable accuracy when they have to recognize their own face. Similarly, one study on an acquired prosopagnosic patient showed preserved trait inferencing from the self-face but not from familiar faces (Klein, Gabriel, Gangi, & Robertson, 2008).…”
mentioning
confidence: 99%